Perlindungan Hukum Pemenang Lelang Atas Objek Lelang Beritikad Baik Yang Di Batalkan Oleh Pengadilan - Iswandi, Holidil; Firdaus, Firdaus; Hendra, Rahmad (Peneliti.net, 2024)
In the auction process that has been carried out, there will be legal consequences, namely the transfer of the rights of the auction object from the seller to the auction winner. In the case of transferring the rights of the auction object, it turns out to cause a problem, such as the auction winner being unable to control the auction object, and the cancellation of the auction based on the decision of the District Court. This research was conducted to find out about the protection of the rights of the auction winner against a court decision canceling the auction and to find out what legal measures can be taken so that the auction winner who has good intentions does not have his rights harmed as a result of the decision to cancel the auction. This type of research is classified as normative legal research. In normative legal research, the data source is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Collecting data on normative legal research uses data collection techniques from a literature study. The data obtained through a literature study will be analyzed qualitatively. In drawing conclusions the author uses the deductive thinking method, namely a way of thinking that draws conclusions from a general statement or argument into a specific statement. Based on the research results, it can be understood that the District Court can cancel the auction for the execution of the Mortgage, the legal consequences arising from the cancellation of the auction for the execution of the Mortgage, as well as the legal protection obtained by the parties involved in the case. The parties can take legal action against the court decision in the event of canceling the auction of mortgage rights, including taking ordinary legal remedies such as resistance/verzet, appeal and cassation. Meanwhile, extraordinary legal remedies that can be taken include Judicial Review and Denderverzet.